2016
DOI: 10.1159/000448271
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid and Neurodevelopmental Outcomes of Term Infants

Abstract: Docosahexaenoic acid (DHA), a long-chain polyunsaturated fatty acid, is essential for normal brain development. DHA is found predominantly in seafood, fish oil, breastmilk and supplemented formula. DHA intake in Western countries is often below recommendations. Observational studies have demonstrated an association between DHA intake in pregnancy and neurodevelopment of offspring but cannot fully adjust for confounding factors that influence child development. Randomised clinical trials of DHA supplementation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…A decade later, the story is still the same: there is little concrete evidence that DHA or DHA supplementation positively affects brain development and function [79][80][81]. Recent reports are mixed.…”
Section: Docosahexaenoic Acidmentioning
confidence: 99%
“…A decade later, the story is still the same: there is little concrete evidence that DHA or DHA supplementation positively affects brain development and function [79][80][81]. Recent reports are mixed.…”
Section: Docosahexaenoic Acidmentioning
confidence: 99%
“…Higher maternal n -3 PUFA status during pregnancy has been associated with lower systolic blood pressure in offspring [ 10 ], increased child height [ 11 ], and better language development [ 12 , 13 ]. However, n -3 PUFA supplementation studies in pregnant women have not consistently supported improved child neurodevelopmental outcomes [ 14 ]. Given the possible influence of maternal PUFA status on child outcomes, it is important that the maternal diet has an optimal balance of PUFA intake during pregnancy to maximise benefits in children.…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopment is usually accompanied by large amounts of DHA accretion in brain, and the peak occurs in the third trimester of pregnancy and lactation (Martinez ). Although the number of brain cells is determined in the fetal period, the size of the brain cells and the connection among neurons such as synaptic formation (Meldrum and Simmer ) and nerve fiber myelination (Benes ; Valk and Knaap ) are still in progress after birth. Recently, a series of behavioral experiments (Moriguchi and others ; Moriguchi & Salem ; Hashimoto and others ; Shirai and others ) showed that DHA intake after weaning could still result in a notable increase in the cerebral DHA level, which consequently improved the n‐3 deficiency‐induced cognitive dysfunction of rats or mice (Fedorova and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a human study (Dalton and others ; Richardson and others ) showed that, in contrast to prenatal and early development, which are known as the critical periods for the beneficial actions of DHA on brain function, DHA could still improve cognitive behavior in healthy children aged 7 to 9 years old. Of note, brain development is nearly completed at 70% by the end of lactation (Meldrum and Simmer ), however, the process still proceeds quickly after weaning, requiring a large number of DHA. Thus, it is necessary to study the rate and efficiency of DHA supplementation on cerebral DHA accretion at this stage.…”
Section: Introductionmentioning
confidence: 99%